The mortal instruments : the graphic novel. 1 - Cassandra Jean.; Clare, Cassandra (New York, NY : Yen Press, 2017)
A graphic novelization of Cassandra Clare's Mortal Instrument series, in which teenager Clary Fray, who has the ability to see demons, is almost killed by a monster, and is pulled into a supernatural world of Shadowhunters and Downworlders and learns terrifying truths about her family.
"Teen, LV"--Back cover.
Based on the Mortal Instruments series by Cassandra Clare.
Young Adult
Young Adult
Keywords: Demonology -- Comic books, strips, etc. -- Juvenile fiction; Magic -- Comic books, strips, etc. -- Juvenile fiction; Supernatural -- Comic books, strips, etc. -- Juvenile fiction; Demonology -- Fiction; Magic -- Fiction; Supernatural -- Fiction; Demonology -- Comic books, strips, etc. -- Fiction; Magic -- Comic books, strips, etc. -- Fiction; Supernatural -- Comic books, strips, etc. -- Fiction; New York (N.Y.) -- Comic books, strips, etc. -- Juvenile fiction; New York (N.Y.) -- Fiction; New York (N.Y.) -- Comic books, strips, etc. -- Fiction; Fantasy comic books, strips, etc; Graphic novels